2007
DOI: 10.1007/s11746-007-1137-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Levels of Lutein and Zeaxanthin in Corn Germ Oil, Corn Fiber Oil and Corn Kernel Oil

Abstract: All commercial corn oil is obtained by pressing corn germ and/or extracting the germ with hexane. In the current study, six types of corn oil were prepared by extracting corn germ, corn fiber and ground corn, each with hexane or with ethanol. The levels of lutein, zeaxanthin and other carotenoids were quantitatively analyzed in the six corn oils. The levels of lutein + zeaxanthin in the oil ranged from 2.3 lg/g for hexane-extracted corn germ oil to 220.9 lg/g for ethanol-extracted ground corn oil. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 18 publications
3
26
2
3
Order By: Relevance
“…Lutein and zeaxanthin have been reported to be present in high levels in the macula portion of the retina, and ingesting at least 6 mg of lutein ? zeaxanthin per day has been reported to be an effective dosage to delay the onset of age-related macular degeneration [8]. The levels of lutein and zeaxanthin were very low in the corn germ oil as we reported previously [8].…”
Section: Analysis Of the Carotenoidssupporting
confidence: 63%
See 2 more Smart Citations
“…Lutein and zeaxanthin have been reported to be present in high levels in the macula portion of the retina, and ingesting at least 6 mg of lutein ? zeaxanthin per day has been reported to be an effective dosage to delay the onset of age-related macular degeneration [8]. The levels of lutein and zeaxanthin were very low in the corn germ oil as we reported previously [8].…”
Section: Analysis Of the Carotenoidssupporting
confidence: 63%
“…Carotenoids were analyzed via a previously reported method [8], employing a LiChrosorb 7 Diol column, 3 9 100 mm (Varian Scientific, Lake City, CA, USA) with an isocratic mobile phase consisting of hexane/isopropanol/acetic acid, 96.9/3.0/0.1, v/v/v, at a flow rate of 0.5 ml/min. HPLC analyses were conducted with an Agilent Model 1100 HPLC equipped with an auto sampler and an Agilent Model 1100 Diode Array Detector to measure the visible absorbance of the carotenoids at 450 nm.…”
Section: Hplc Analysis Of Carotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an almost complete loss of carotenoids during the bleaching with diminishing colour intensity of the oil. Rossi et al [27] made similar statements for palm oil, Su et al [28] did so for olive oil as Moreau et al [29] stated this bleaching induced carotenoid loss for corn oil.…”
Section: Carotenoids In Oils Seeds and Presscakeschromatographic Detmentioning
confidence: 90%
“…Regarding the absence of carotenoids in refined oils, previous technological studies have shown that carotenoids are removed from the crude oil by various refining steps [21,[25][26][27][28][29]. The bleaching earth adsorbs the plant pigments, additionally a thermal deterioration happens during the deodorization [25].…”
Section: Carotenoids In Oils Seeds and Presscakeschromatographic Detmentioning
confidence: 99%